Mengukur Kuasa Fikih dan Teologi Atas Pemikiran: Studi Kasus Fatwa Pengharaman Liberalism, Sekularisme, dan Pluralisme - Agus Ahmad Sua’idi (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Islamic law (fiqh) can penalize every actual deviance done by people in is sovereignty. The deviance in this case is a concept about the action that breaks existing laws accepted widely by a Muslim community. But Islamic law can do that only if the certain action evenly influents to others. Thinking is cerebral and mental doings not practice and sometime it cannot be stopped as long as the fascinating answer and not yet been gained. But undoubtedly, a though as fruit of thinking especially of well-know individuals, has bigger, wider, and more influence to others than an action has. If the impact is considered as bad due to public or religious authority, the thought and its thinker occasionally will be punished in many ways, Is it proper when a certain authority monitors, examines, and judges the thoughts spreading and if necessary punishes the thinkers when deemed ‘’dangerous’’? Should such thought be classified haram or heretic? How much power does Islamic law truly has? These are many questions need to be responded that we know our right to free thinking and understand when we ought to restrict it.